Dinamika Tradisi Marpangir di Kabupaten Padang Lawas Utara, 1990-2000 - Siregar, Nurhafifah; Siregar, Yusra Dewi; Naldo, Jufri (Local History & Heritage, 2023)
This research examines the "Dynamics of the Marpangir Tradition within the North Padang Lawas Regency Community" with a primary focus on its historical emergence and evolving dynamics during the period from 1990 to 2000. Employing qualitative methods, including an anthropological approach and ethnographic data collection through observation, interviews, and documentation, this study draws from seven informants representing diverse backgrounds, such as community leaders, tradition practitioners, and local authorities. The findings highlight the Marpangir Tradition as a customary practice in North Padang Lawas Regency, serving as a purification ritual preceding Ramadan fasting. Despite its long-standing presence in local culture, significant transformations have occurred between 1990 and 2000, including the adoption of practical alternatives like shampoo and soap due to challenges in sourcing traditional ingredients. Furthermore, a shift in community engagement is observed, with more young individuals utilizing the tradition for social interactions and even dating, offering valuable insights into the adaptability of cultural traditions in response to changing societal values.